High rabies burden and low vaccination status among dogs inflicting bite in Addis Ababa: an urgent call for action - Abdella, Sintayehu; Ahmed, Khogali; Salim, Bienvenu; Ashenefe, Baye; Mulugeta, Yimere; Girma, Endalkachew; Aklilu, Mesefin; Getachew, Abebe; Kitila, Gutu; Getahun, Garuma; Berihanu, Endalkachew; File, Ibsa; et al. (The Journal of Infection in Developing Countries, 2022)
Introduction: Rabies remains a global threat, killing approximately 60,000 people every year. In Ethiopia, dogs are the main reservoir of the disease. Animals also estimate the burden of the disease. Methodology: Data from 2016 to 2020 were extracted from a rabies cases recording book of the Ethiopian Public Health Institute. Proportions and trends over time were analyzed. Brain samples of dogs were diagnosed with a Fluorescent Anti Body test. Results: A total of 6,001 dogs inflicting bites were brought to the laboratory. A high proportion of dogs 4,389 73.14% were not vaccinated. The total number of dogs brought to the laboratory was decreasing over the last five years. Among 1,216 dog brain samples examined 855 (70.3%) confirmed rabies. The proportion of rabies cases was increasing from 8.5% in 2016 and 32.6% in 2020. The highest rabies proportion (33.8%) was reported in 2018. Out of the total (2,156) dogs inflicting bites and observed for 10 days, only 468 (21.7%) of the observation report was tracked and reported. Conclusions: There is a high proportion of rabies in dogs inflicting bites in Addis Ababa. The findings are alarming with seven out of ten dogs diagnosed being infected with rabies. Only two dogs were vaccinated out of ten dogs inflicting bites. Rabies became a serious public health problem in the city that needs urgent health action from all sectors including the city administration.